The influence of external ultrasound on the histologic architecture of the organic capsule around smooth silicone implants: Experimental study in rats - Mendes, F. H.; Viterbo, Fausto [UNESP]; DeLucca, L. (Springer, 2008)
Background Capsular contracture is the main complication related to breast silicone implants, and its prevention remains a medical challenge. The authors present experimental research examining the effect of external ultrasound on the formation and contracture of peri-implant capsules.Methods In this study, 42 male Wistar rats had a 2-mm smooth surface implant placed in a dorsal submuscular pocket. They then were separated into ultrasound'' and control'' groups that received repeated external applications either with or without the ultrasound power on. Ultrasound applications were given three times a week for a period of 90 days. After that, both groups were housed under the same conditions with no application scheduled. Five animals of each group, killed at 30, 60, 90, and 180 days, had their implants removed along with the capsule, which received a special histologic preparation via annular sectioning that provided wide circumferential observation of the capsular tissue. Sections were stained with hematoxylin/eosin stain, Masson's trichrome stain, and Pricrosirius Red stain for regular microscopic evaluation under normal and polarized light.Results Histologic data showed that capsules from the ultrasound and control groups had statistically significant differences. Ultrasound application developed a capsular architecture similar to that shown within textured silicone implants, and its effect had an early definition with subsequent stabilization.Conclusion The authors conclude that early and repeated external ultrasound application enhances the thickness, cellular count, and vascularity of smooth silicone capsular tissue, whereas it diminishes the pattern of parallel orientation of collagen fibers.
Keywords: breast silicone implants; capsular contracture; external ultrasound